Memories of violence among public secondary school students in Acapulco (2000–2025) - DORANTES NAZARIO , Claudia Araceli (Utopía y Praxis Latinoamericana, 2025)
The objective of this research is to explore the consequences of violence and bullying in shaping critical subjectivities (active and rebellious youth citizenship) in the memories of affected individuals, particularly those in public secondary schools in Acapulco. It theorizes that today's secondary school students construct a critical memory and an active and rebellious citizenship in the face of structural violence, institutional neglect, and educational insecurity. Pedagogies of memory were examined as tools for political resistance and citizenship building. A mixed methodology was employed, including surveys, interviews, documentary analysis, and a literature review. It also proposes an articulation between critical theory, emancipatory pedagogy, and empirical data analysis to understand the phenomenon of bullying as part of a broader framework of structural violence. The study highlights the active role of youth in the production of insurgent memories, their capacity for agency in adverse contexts, and the urgency of a comprehensive educational and community response. The research seeks to contribute to the formulation of public policies that are sensitive to the local context and to the transformation of schools into spaces of care and justice. Finally, the paper reflects on the need for an affective pedagogy that recognizes youth memories as tools of cultural and political resistance. The methodology used consisted of a mixed-method approach, combining quantitative methods (structured surveys of high school students) and qualitative methods (in-depth interviews, participant observation, and documentary analysis).